Factors of the Inflation in Nepal - Humagai, Reem Prasad (Patan Prospective Journal, 2023)
This study examines the impacts of macroeconomic variables on the inflation in Nepal during 1975-2022. The variables considered for the study is limited to the use of broad money supply, real GDP, Indian prices. The results suggest that all variables considered are significant in long run implying that these variables are the determinants of inflation in Nepal. The results are consistent with monetary theory. The money supply and Indian prices cause inflation in the long-run based on an Ordinary Least Squares regression model. The empirical results show that in the long-run, the major determinants of inflation in Nepal are Indian inflation (0.453), real income (0.347),and exchange rate (0.224). In addition, Indian inflation (0.286), the exchange rate (0.141), and government deficit (0.039) have significant effects in the short-run. Finally, the error correction term is found to be negative and statistically significant suggesting a correction of short-run disequilibrium within two years.